2005
DOI: 10.1080/00498250400028247
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the metabolites of alosetron in experimental animals and human

Abstract: The metabolism of radiolabelled alosetron was studied in rat, dog, rabbit, mouse and human. The metabolism in rat and dog was studied at a low and an elevated dose designed to generate sufficient quantities of metabolite for definitive identification. A strategy for the characterization of metabolites in cases of extensive metabolism was developed and demonstrated for alosetron. Semi-preparative high-performance liquid chromatography (HPLC), liquid chromatography-mass spectrometry (LC-MS), nuclear magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Quantitative differences in the production of metabolites of the 5HT 3 antagonists were apparent between in vitro systems. Neither microsomes nor hepatocytes completely reflected the quantitative in vivo metabolite profile of the 5HT 3 antagonists as previously reported in pre-clinical species or human (Wolf 2000;Koch et al 2004;Ismail et al 2005). In general, the production of more lipophilic, CYP3A4 mediated metabolites, especially carbonyl metabolites, predominated in microsomes compared with hepatocytes.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Quantitative differences in the production of metabolites of the 5HT 3 antagonists were apparent between in vitro systems. Neither microsomes nor hepatocytes completely reflected the quantitative in vivo metabolite profile of the 5HT 3 antagonists as previously reported in pre-clinical species or human (Wolf 2000;Koch et al 2004;Ismail et al 2005). In general, the production of more lipophilic, CYP3A4 mediated metabolites, especially carbonyl metabolites, predominated in microsomes compared with hepatocytes.…”
Section: Discussionmentioning
confidence: 51%
“…*metabolites previously identified in human liver micosomes. metabolites due to multiple sequential oxidation of alosetron previously reported in animals and human (Ismail et al 2005) were not observed as major metabolites in rat and dog microsomes or hepatocytes. A number of minor mono-oxygenated metabolites of alosetron were detected but were not given definitive structural assignments owing to lack of fragmentation information.…”
Section: Metabolite Profiles Of Ondansetron Alosetron and Gr87442 Inmentioning
confidence: 70%
See 2 more Smart Citations
“…Analytical (4.6 mm) columns can support larger injections but also dilute the eluted sample as presented to the NMR detection region. The combination of HPLC and online SPE (70,71) for concentration of dilute samples prior to introduction to a capillary or cryogenic (72) probe NMR appears the best current alternative to full (73) or partial (74) offline isolation. In a very rare case, X-ray crystallography (75) can be used to exactly define metabolite stereochemistry in systems where even NMR fails to define all atom positions.…”
Section: Nmr and Structure Confirmationmentioning
confidence: 99%